Do motor performance and specific-skill tests discriminate technical efficiency in small-sided games? - Julio Cesar da Costa; Paulo Henrique Borges; Luiz Fernando Ramos-Silva; Vinícius Muller Reis Weber; Felipe Arruda Moura; Alexandre Moreira; Enio Ricardo Vaz Ronque (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: The aim was to compare performance in specific-skill tests and motor coordination between groups with different technical efficiency and verify possible variables related to specific skills and motor coordination that contribute to discriminate players into high- and low-technical efficiency. Methods: The sample consisted of 82 young soccer players (12-15 years). Body size, bone age, motor performance tests, soccer-specific skill tests, and frequency of technical actions in SSG were analyzed. Statistic cluster-derived ANOVA F was used to identify which variables related to technical action most contributed to classifying subjects with similar performance. Discriminant analysis (Stepwise Method) was used to verify which predictor variables discriminated players into groups of low- and high-frequency technical actions in SSG. Statistical significance was set at 5%. Results: The group of high technical efficiency presented better performance in motor tests, shuttle run (P = 0.04; ES = −0.55), jumping laterally (P = 0.02; ES = 0.58), kicking speed (P = 0.03; ES = 0.60), soccer-specific skill tests, leading the ball in a straight line (LBSL) (P = 0.01; ES = −0.75), and zig-zag ball control (ZZBC) (P = 0.04; ES = −0.55); variable leading the ball in a straight line correctly discriminated 60% of players into high- and low-frequency groups. Conclusion: The frequency of technical actions in SSG was poorly influenced by motor performance and specific skill tests, and only the LBSL test correctly classified players of different frequencies of technical actions in SSG.